Peningkatan Literasi Keuangan Syariah dan Pemasaran Digital pada Pelaku UMKM di Desa Lasem, Sedyu, Gresik - Lantip Lantip; Muhlis Muhlis (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This study aims to analyze strategies for improving Islamic financial literacy and the utilization of digital marketing among Micro, Small, and Medium Enterprises (MSMEs) in Lasem Village, Sidayu District, Gresik Regency. The research employed a descriptive qualitative method with a case study approach through mentoring in the form of Islamic financial literacy and digital marketing training. The research subjects consisted of 15 MSME actors engaged in food, handicrafts, and services. Data were collected through in-depth interviews, participatory observation, pre- and post-training questionnaires, and documentation. The results indicate a significant improvement in both understanding and practices of the MSME participants. In terms of Islamic financial literacy, participants who previously tended to mix business and personal finances have begun to apply separate bookkeeping, avoid interest-based (riba) practices, and develop awareness of zakat/infaq obligations. Meanwhile, in terms of digital marketing, participants who initially had very limited use of technology are now actively utilizing platforms such as WhatsApp Business, Instagram, and online marketplaces for promotion and sales. The pre- and post-training questionnaires show an increase from 20% to 87% of participants in the good–very good category of Islamic financial literacy, and from 13% to 80% in the utilization of digital marketing. This study concludes that the integration of Islamic financial literacy and digital marketing not only enhances financial and marketing capacities but also strengthens the competitiveness of rural MSMEs. These findings provide practical contributions to the development of MSME empowerment programs based on Islamic economics and digital innovation in other regions.